Network-centric computing : preparing the enterprise for the next millennium - Varhol, Peter D. (Computer Technology research CharlestownUS, 1998)
Covers the background leading to the advent of network-centric computing technologies and trends. Explains how the Java programming language enables network computing, the details of the thin-client concept, and how the network computer hardwear brings the pieces of the strategy together. Concludes with an examination of the exploding field of non-desktop network computing devices, such as set-top boxes, cellular telephones, and personal digital assistants, that have been enabled by Java and the Web.